Digital marketing trends in Bangladesh: a measure of sheba.xyz’s efficiency on executing these trends - Khan, Ashiqul Haque (Brac University, 2020)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.